If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -5 = -1y + 21 + 7 Combine like terms: 4 + -5 = -1 -1 = -1y + 21 + 7 Reorder the terms: -1 = 21 + 7 + -1y Combine like terms: 21 + 7 = 28 -1 = 28 + -1y Solving -1 = 28 + -1y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add 'y' to each side of the equation. -1 + y = 28 + -1y + y Combine like terms: -1y + y = 0 -1 + y = 28 + 0 -1 + y = 28 Add '1' to each side of the equation. -1 + 1 + y = 28 + 1 Combine like terms: -1 + 1 = 0 0 + y = 28 + 1 y = 28 + 1 Combine like terms: 28 + 1 = 29 y = 29 Simplifying y = 29
| 8x+4(1.5x)=53.84 | | 2w^3=8 | | (5x+40)(4x-20)=0 | | 8/5(x)=24 | | -2=(x-100)/15 | | 10x-2=5x+3 | | 2w^2=8 | | 18x=138 | | 8x+4(1.5x)=115.38 | | ((-x/y)1/3)6) | | 8x+4(1.5x)=11.38 | | 2=(x-100)/15 | | -y+12=47 | | 0.76(8b+4)-2=4b+14 | | 6t+5=55 | | 8x+4(1.5x)=116 | | 4/(3w)=x/(9w^9) | | 2n-3=0 | | 3v+s=S+2v+v | | 6x-0=-14 | | 4/3w=x/9w^9 | | -4=1/4x | | y-4y+3y=0 | | E^2x+1=13 | | 65/7 | | 40-2p=p-5 | | 6/5/7 | | x^2+kx-4=-k+x+1f | | 40-2p=-5+p | | 3x+4x=27 | | 2x+7=x+x+7 | | 2x+4x+18=25 |